Design and Control of a Seaweed Dryer Prototype Powered by Solar and Wind Energy - Setiyono Setiyono; Elfitrin Syahrul; Dyah Nur’ainingsih (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2026)
Seaweed drying is a crucial step in maintaining product quality and shelf life. However, conventional methods still face significant challenges, including high energy consumption, reliance on fossil fuels, and instability in quality due to environmental variability. This research developed a prototype hybrid-powered seaweed dryer that simultaneously utilizes solar and wind energy and is equipped with an automated control system to monitor and regulate temperature and humidity during the drying process. The prototype canoperate in both manual and automatic modes, making it suitable for small-scale production and off-grid environments. Test results demonstrated that the prototype can effectively utilize hybrid renewable energy sources while maintaining adaptive protection and control based on environmental conditions, offering a cost-effective and environmentally friendly solution for small-scale seaweed farmers This article presents measurable results in the form of output voltage, current, and power generated by the solar panel andwind turbine, which demonstrate the capability of the hybrid energy system to supply power for the seaweed dryer. The novelty of this research lies in the integration of dual energy sources with an automated control system, which has not been widely implemented in previous seaweed dryers. This approach improves energy efficiency, lowers operational costs, and offers a sustainable solution for seaweed production, while supporting the development of environmentally friendly drying technologies.